Pengaruh Teknologi Blockchain Terhadap Proses Audit - Bambang Wahyudi; Milatina Laksmita Dewi; Nurifa Laksmitasari Azizah (Journal of Applied Accounting And Business, 2025)
Blockchain technology has a significant impact on audit practices, especially in improving the efficiency, effectiveness, and reliability of financial information. This technology offers advantages in the form of data transparency, transaction immutability, and real-time access that allow audits to be carried out continuously. This study aims to examine the influence of blockchain technology on the audit process and identify the challenges and opportunities for its implementation in the context of audit practices in Indonesia. The method used is a systematic literature review of various accredited scientific publications over the past decade (2014–2024). The results of the study show that blockchain is able to accelerate the data verification process, minimize the risk of errors, and encourage integration between accounting and audit systems. However, the implementation of this technology still faces obstacles in the form of limited technical competence of auditors, uneven infrastructure, and the need to adapt to a digital-based audit approach. Therefore, a capacity building strategy and increasing technological literacy are needed in the accounting profession to support optimal blockchain implementation